2016
DOI: 10.1177/1087054715611493
|View full text |Cite
|
Sign up to set email alerts
|

Association of ADHD and Celiac Disease: What Is the Evidence? A Systematic Review of the Literature

Abstract: Up till now, there is no conclusive evidence for a relationship between ADHD and CD. Therefore, it is not advised to perform routine screening of CD when assessing ADHD (and vice versa) or to implement gluten-free diet as a standard treatment in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…In addition, the We evaluated the symptoms related to the tics and the OCD using questionnaires that are widely validated and accepted internationally. However, we did not evaluate the symptoms related to ADHD, although we also found that they improved while on the GFD, as has been confirmed in a recent systematic review of this subject [49].…”
Section: Discussionmentioning
confidence: 65%
“…In addition, the We evaluated the symptoms related to the tics and the OCD using questionnaires that are widely validated and accepted internationally. However, we did not evaluate the symptoms related to ADHD, although we also found that they improved while on the GFD, as has been confirmed in a recent systematic review of this subject [49].…”
Section: Discussionmentioning
confidence: 65%
“…We evaluated the symptoms related to the tics and the OCD using questionnaires that are widely validated and accepted internationally. However, we did not evaluate the symptoms related to ADHD, although we also found that they improved while on the GFD, as has been confirmed in a recent systematic review of this subject [ 49 ].…”
Section: Discussionmentioning
confidence: 79%
“…Although the relationship between CD and ADHD/ASD is not well established [2,3,4], a repeated clinical feature noted in CD is the elevated levels of NO in serum and urine [5,6,7,8]. A recent meta-analysis reporting on oxidative stress in ADHD found elevated NO in the blood of ADHD subjects [9], and similar findings have been made on levels of plasma NO in ASD [10].…”
mentioning
confidence: 83%